THE POLITICS OF LAND LAW AND THE IMPLEMENTATION OF THE AGRARIAN REFORM PROGRAM IN INDONESIA - Jesse Heber Ambuwaru; Bintan R. Saragih; Listyowati Sumanto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Agrarian reform is primarily aimed at overcoming inequality in land ownership, realizing legal certainty, prosperity and welfare for the whole community. The research objective is to describe howthe development of agrarian politics related to agrarian reform, the implementation of agrarian reform in Indonesia and the obstacles faced in implementing agrarian reform. This type of normative legal research is descriptive and the statute approach and concept approach are used in this study. Secondary data that has been collected is analyzed qualitatively, and conclusions are drawn using deductive logic. The results of the study show that the politics of agrarian law related to agrarian reform in the Old Order, New Order and Reform Order eras have led to efforts to realize equal distribution of prosperity for all people. The implementation of agrarian reform achieved success achieved by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency through the acceleration of the Agrarian Reform Object Land and Complete Systematic Land Registration programs which always reach the target every year. It is targeted that in 2025 all land parcels in Indonesia will have been certified through the Complete Systematic Land Registration program. There are various internal and external obstacles faced in implementing agrarian reform.